Formal Islamic Boarding School Education: A Normative Study of PDF, SPM and Ma'had Aly - Nurul Huda (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article aims to explain the status of formal Pesantren educational institutions which have yet to gain widespread public recognition despite seven years having passed since the enactment of Law No. 18 of 2019 concerning Pesantren, or even twelve years since the issuance of the Minister of Religious Affairs Regulation No. 13 of 2014 concerning Islamic Religious Education. This study employs a qualitative, normative library research approach, referencing the regulations governing formal Pesantren institutions specifically Pendidikan Diniyah Formal (PDF) and Satuan Pendidikan Muadalah (SPM) across primary levels (Ula and Wustha), secondary levels (Ulya), and higher education levels (Ma’had Aly). While some existing literature on these formal institutions relies on regulations predating the Pesantren Law specifically the Minister of Religious Affairs Regulation derived from Government Regulation No. 55 of 2007 this study offers a distinct perspective by focusing on the regulatory framework established after the enactment of Law No. 18 of 2019. Ultimately, this research seeks to address the needs of the Pesantren community by filling a gap that existing formal education systems namely schools under the Ministry of Education and madrasas under the Ministry of Religious Affairs have been unable to meet. It is hoped that future research will expand beyond a single type of formal education and incorporate both existing and updated legal frameworks.